The impact of ADHD and social anxiety on academic performance among college Students in Iceland - Elísabet Freyja Þorleifsdóttir 2001- (2024)
Attention deficit hyperactivity disorder (ADHD) and social anxiety disorder are common mental disorders that can have a significant impact on an individual's life, including academic performance. University students face a variety of challenges when it comes to their studies, and the aim of this study is to investigate whether there is a relationship between ADHD, social anxiety, and academic performance among university students in Iceland. ADHD symptoms were measured with the ADHD-RS self-assessment scale and social anxiety symptoms with the SIAS-6 and SPS-6 self-assessment scales. The research questions were 1) Does ADHD affect academic performance? 2) Does ADHD affect social anxiety? 3) Does social anxiety affect academic performance? 4) Does social anxiety mediate the relationship between ADHD and academic performance? The study was part of a larger cross-sectional study conducted by Reykjavík University (RU) that examined the well-being of university students at RU. The sample was selected based on convenience, as all registered students in RU responded to an online survey that they received via their RU email. The current study used responses from 402 students, aged 18 to 57. The result suggests that both ADHD and social anxiety symptoms are related to academic performance, but ADHD symptoms have a more significant direct impact. Social anxiety symptoms also play a role, but their effect is less pronounced and not statistically significant. Keywords: ADHD, social anxiety, academic performance, university students Athyglisbrests- og ofvirkniröskun (ADHD) og félagskvíði eru algengar geðraskanir sem geta haft veruleg áhrif á líf einstaklings, þar á meðal á námsárangur. Háskólanemar þurfa að takast á við allskonar áskoranir þegar kemur að náminu og er markmið þessarar rannsóknar að kanna hvort tengsl séu á milli ADHD, félagskvíða og námsárangurs meðal háskólanema á Íslandi. ADHD einkenni voru mæld með ADHD-RS sjálfsmatskvarðanum og einkenni félagskvíða með SIAS-6 og SPS-6 sjálfsmatskvörðunum. ...